PHYSICAL TRAINING OF YOUTHS WITH THE MEANS OF ATHLETIC GYMNASTICS. (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the role of using athletic gymnastics equipment in improving the physical fitness of young people before conscription. It covers the content, main equipment, importance of athletic gymnastics in the life of young people before conscription, and principles of effective organization of training. The article pays special attention to the issues of raising young people to be healthy, strong and strong-willed, as well as increasing their readiness to defend the Motherland.